Growth of porous single-crystalline molybdenum nitrides microcubes with enhanced electrocatalysis performance. (18th June 2021) - Yunqi, Su; Jiaming, Li; Guoming, Lin; Kui, Xie
Abstract: Porous single crystal has the characteristics of long-range order, continuous lattice and large specific surface area, which could reduce energy losses and keep high activity and stability in electrochemical systems. Here, we grow porous single-crystalline and polycrystalline molybdenum nitrides microcubes from MoO3 single crystals. These porous microcubes show superior HER and OER performance. The overpotential of Mo2 N porous single crystal microcubes is only 73.13 mV at a current density of 10 mA cm −2, which is 150.53 mV, 192.76 mV and 255.87 mV lower than that of MoN single crystal, Mo2 N polycrystal and MoN polycrystal, respectively. The advantages of Mo2 N porous single crystals in electrocatalytic properties are also reflected in OER. Graphical abstract: Image 1 Highlights: A new way to synthesize porous single crystals of molybdenum nitrides. Molybdenum nitrides have a good performance in HER. Porous single crystal performs high activity and stability in HER and OER.